Elucidating the Origins of High Preferential Crystal Orientation in Quasi‐2D Perovskite Solar Cells. Issue 5 (5th December 2022) - Lehner, Lukas E.; Demchyshyn, Stepan; Frank, Kilian; Minenkov, Alexey; Kubicki, Dominik J.; Sun, He; Hailegnaw, Bekele; Putz, Christoph; Mayr, Felix; Cobet, Munise; Hesser, Günter; Schöfberger, Wolfgang; et al.
Abstract: Incorporating large organic cations to form 2D and mixed 2D/3D structures significantly increases the stability of perovskite solar cells. However, due to their low electron mobility, aligning the organic sheets to ensure unimpeded charge transport is critical to rival the high performances of pure 3D systems. While additives such as methylammonium chloride (MACl) can enable this preferential orientation, so far, no complete description exists explaining how they influence the nucleation process to grow highly aligned crystals. Here, by investigating the initial stages of the crystallization, as well as partially and fully formed perovskites grown using MACl, the origins underlying this favorable alignment are inferred. This mechanism is studied by employing 3‐fluorobenzylammonium in quasi‐2D perovskite solar cells. Upon assisting the crystallization with MACl, films with a degree of preferential orientation of 94%, capable of withstanding moisture levels of 97% relative humidity for 10 h without significant changes in the crystal structure are achieved. Finally, by combining macroscopic, microscopic, and spectroscopic studies, the nucleation process leading to highly oriented perovskite films is elucidated. Understanding this mechanism will aid in the rational design of future additives to achieve more defect tolerant and stable perovskite optoelectronics. Abstract : The nucleation process to form quasi‐2D perovskites is thermodynamically controlled using the methylammonium chloride additive to achieve films with a degree of preferential orientation of 94%, capable of withstanding 97% relative humidity for 10 h without degradation. Combining microscopic, macroscopic, and spectrographic observations, the thermodynamics enabling preferential crystal growth are inferred.